2013
DOI: 10.1016/j.neurobiolaging.2012.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Trophic factors differentiate dopamine neurons vulnerable to Parkinson's disease

Abstract: Recent studies suggest a variety of factors characterize substantia nigra neurons vulnerable to Parkinson's disease, including the transcription factors Pitx3 and Otx2 and the trophic factor receptor DCC, but there is limited information on their expression and localisation in adult humans. Pitx3, Otx2 and DCC were immunohistochemically localised in the upper brainstem of adult humans and mice and protein expression assessed using relative intensity measures and online microarray data. Pitx3 was present and hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 53 publications
(57 reference statements)
1
39
0
1
Order By: Relevance
“…; Reyes et al . ), is involved in the generation and maintenance of the elaborate axonal arborization of these neurons. It is known that DCC regulates the guidance of SNc and VTA dopaminergic axons to the striatum via its interaction with netrin (Li et al .…”
Section: Diversity Of Neurons In the Ventral Mesencephalic Dopaminergmentioning
confidence: 99%
“…; Reyes et al . ), is involved in the generation and maintenance of the elaborate axonal arborization of these neurons. It is known that DCC regulates the guidance of SNc and VTA dopaminergic axons to the striatum via its interaction with netrin (Li et al .…”
Section: Diversity Of Neurons In the Ventral Mesencephalic Dopaminergmentioning
confidence: 99%
“…DCC expression in dopamine neurons is high during early development and adolescence, in line with the maturational timeline of dopamine pathways. Interestingly, DCC expression is substantially lower during adulthood, suggesting that DCC signaling may play a different, more local, role in the adult brain (Osborne et al, 2005;Grant et al, 2007;Manitt et al, 2010;Reyes et al, 2013;Yetnikoff et al, 2007Yetnikoff et al, , 2010Yetnikoff et al, , 2011Yetnikoff et al, , 2013a. Using rodents, we showed that DCC signaling within the ventral tegmental area (VTA) dopamine neurons determines the extent of their innervation to the mPFC specifically during adolescence and, in turn, organizes the structure and function of mPFC local circuitries (Manitt et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Although both SNC and VTA subtypes express Pitx3 during terminal differentiation 143, 144 and in aged humans, 206 only the SNC, in terms of survival, requires expression of Pitx3 . 68, 186, 207 Pitx3 supresses the intrinsic expression of En1 and thereby of posterior markers such as CCK in SNC DN.…”
Section: Resultsmentioning
confidence: 99%
“…Medial and paramedial mesodiencephalic floor plate progenitors generate DN in the SNC and VTA, respectively. Both express Pitx3 , 143, 144, 206 but knock-out of Pitx3 results in selective loss of SNC neurons, 68, 186, 207 so Pitx3 expression is required for the development of the SNC but not required for the VTA.…”
Section: Discussionmentioning
confidence: 99%